A Multisensor Integration Approach toward Astronaut Navigation for Landed Lunar Missions. Issue 2 (10th November 2013) - Li, Rongxing; He, Shaojun; Skopljak, Boris; Meng, Xuelian; Tang, Pingbo; Yilmaz, Alper; Jiang, Jinwei; Oman, Charles M.; Banks, Martin; Kim, Sunah
<x xml:space="preserve">Abstract</x> As experienced by Apollo lunar astronauts, spatial orientation can be affected significantly by lunar environmental conditions such as the moon's altered gravity, lack of an atmosphere, limited spatial references, and different level of reflectivity. To help overcome these challenges, a lunar astronaut navigation system called LASOIS (Lunar Astronaut Spatial Orientation and Information System) has been developed. It can significantly reduce spatial disorientation and improve real‐time navigation capability for astronauts exploring the lunar surface. LASOIS is capable of integrating satellite imagery and sensors mounted on the astronaut spacesuit (including inertial measurement units, stereo cameras, and pressure sensors) by an extended Kalman filter algorithm. The processed navigation information is presented through a wrist‐mounted display system. The system has been tested at three field experiment sites, including Moses Lake, WA, Black Lava Point, AZ, and Haleakala National Park, HI. It is demonstrated that the system has achieved an error rate (or relative accuracy) of 2.4% for astronaut navigation over a traverse of 6.1 km in a lunarlike environment.